Paediatric pre‐B acute lymphoblastic leukaemia‐derived exosomes regulate immune function in human T cells. Issue 16 (13th July 2022) - Gholipour, Elham; Kahroba, Houman; Soltani, Nasim; Samadi, Parisa; Sarvarian, Parisa; Vakili‐Samiani, Sajjad; Hosein Pour Feizi, Abbas Ali; Soltani‐Zangbar, Mohammad Sadegh; Baghersalimi, Adel; Darbandi, Bahram; Movassaghpour, Aliakbar; Talebi, Mehdi; et al.
Abstract: Exosomes derived from solid tumour cells are involved in immune suppression, angiogenesis and metastasis; however, the role of leukaemia‐derived exosomes has less been investigated. Hence, changes in immune response‐related genes and human T cells apoptosis co‐incubated with exosomes isolated from patients' pre‐B cell acute lymphoblastic leukaemia were evaluated in this in vitro study. Vein blood sample was obtained from each newly diagnosed acute lymphoblastic leukaemia (ALL) patient prior any therapy. ALL serum exosomes were isolated by ultrafiltration and characterized using Western blotting and transmission electron microscopy. Exosomes were then co‐incubated with T lymphocytes and the gene expressions, as well as functions of human T cells were quantified by qRT‐PCR. Apoptosis and caspase‐3 and caspase‐9 protein expression were also evaluated by flowcytometry and Western blotting analysis, respectively. Exosomes isolated from ALL patients affected T lymphocytes and elevated the apoptosis. Moreover, these exosomes altered the T cells profile into regulatory type by increasing the expression of FOXP3 and Tregs‐related cytokines, including TGF‐B and IL‐10. The expression level of Th17‐related transcription factors (RoRγt) and interleukins (IL‐17 and IL‐23) decreased after this treatment. According to our findings, exosomes derived from ALL patients' sera carry immunosuppressive molecules, indicating the possible effect of exosomes as liquid biomarkers for cancer staging.